Extraordinary Temperature Dependent Second Harmonic Generation in Atomically Thin Layers of Transition‐Metal Dichalcogenides. Issue 17 (25th May 2020) - Khan, Ahmed Raza; Liu, Boqing; Zhang, Linglong; Zhu, Yi; He, Xin; Zhang, Lijun; Lü, Tieyu; Lu, Yuerui
Abstract: Atomically thin transition metal dichalcogenides (TMDs) are important semiconducting materials because of their interesting layer dependent properties. Recently, optical second harmonic generation (SHG) is used to probe layer number, lattice orientation, phase variation, and strain vector in ultrathin TMDs. Here, it is demonstrated that SHG response of ultrathin TMDs is highly sensitive to temperature modulation. Furthermore, temperature dependent SHG is found to show opposite trends for single layer and few odd layers (3L, 5L, 7L, etc.) of TMDs. A remarkable temperature dependent SHG enhancement (25.8%) is found in single layer molybdenum diselenide (MoSe2 ) using 900 nm laser excitation whereas few odd layers show significant temperature dependent SHG quenching which is found to be ‐55.2%, ‐31.02%, and ‐18.4% in case of 3L, 5L, and 7L of MoSe2 . Temperature dependent SHG investigation with other TMDs, like MoS2, WS2, and WSe2, shows the similar trend which reveals an important structural characteristic for TMDs. Second order nonlinear susceptibility calculations considering weak van der Waal forces during thermal expansion in ultrathin TMDs show good agreement with the experimental findings. The results show SHG as a powerful and sensitive approach to investigate thermal variation in ultrathin TMDs. Abstract : Highly sensitive temperature dependent second harmonic generation (SHG) response is shown in atomically thin layers of transition‐metal dichalcogenides (TMDs) through multiphoton microscopy. A significant temperature dependent SHG enhancement and SHG quenching is observed for single layer and few odd layers (3L, 5L, 7L, etc.), respectively, for TMDs. This research enables novel applications of TMDs in nonlinear optical devices.